Integración de los estudiantes con necesidades educativas especiales en el proceso de aprendizaje de los octavos, noveno y décimo año de educación básica de la Unidad Educativa Ismael Pérez Pazmiño de la ciudad de Machala en el periodo lectivo 2012. - Alvarado Campuzano, Ginger Johanna (2012)
During the research process it was determined that in the educational unit there is a negative impact on the integration of students with special educational needs so that the knowledge of the teaching staff are not in order to work in this area.